2009
DOI: 10.1088/0004-637x/701/2/l75
|View full text |Cite
|
Sign up to set email alerts
|

An Unstable Superfluid Stewartson Layer in a Differentially Rotating Neutron Star

Abstract: Experimental and numerical evidence is reviewed for the existence of a Stewartson layer in spherical Couette flow at small Ekman and Rossby numbers (E 10 −3 , Ro 10 −2 ), the relevant hydrodynamic regime in the superfluid outer core of a neutron star. Numerical simulations of a superfluid Stewartson layer are presented for the first time, showing how the layer is disrupted by nonaxisymmetric instabilities. The unstable ranges of E and Ro are compared with estimates of these quantities in radio pulsars that exh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Turbulence, on the other hand, is well known from laboratory superfluids and may play an important role in pulsar glitches (Peralta et al ; Melatos & Peralta ; Peralta & Melatos ) and could couple the superfluid and the normal component on inter‐glitch time‐scales in the presence of core pinning (Andersson, Sidery & Comer ). The inclusion of turbulence in a hydrodynamical glitch simulation is, however, a complex matter as not only is the nature of the turbulence not known (see e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Turbulence, on the other hand, is well known from laboratory superfluids and may play an important role in pulsar glitches (Peralta et al ; Melatos & Peralta ; Peralta & Melatos ) and could couple the superfluid and the normal component on inter‐glitch time‐scales in the presence of core pinning (Andersson, Sidery & Comer ). The inclusion of turbulence in a hydrodynamical glitch simulation is, however, a complex matter as not only is the nature of the turbulence not known (see e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While it is unknown what triggers the collective unpinning, it is likely to excite a non-axisymmetric flow for two generic reasons. (1) Pinning causes the crust and superfluid to rotate differentially, inevitably driving non-axisymmetric meridional circulation and even turbulence, as observed in laboratory experiments (Munson & Menguturk 1975;Nakabayashi 1983;Junk & Egbers 2000) and numerical simulations (Peralta et al 2005(Peralta et al , 2006aMelatos & Peralta 2007;Peralta et al 2008;Peralta & Melatos 2009) of spherical Couette flow.…”
Section: Introductionmentioning
confidence: 99%
“… Peralta et al (2006b) showed that this is inaccurate at high Reynolds numbers, when meridional circulation and Kolmogorov‐like turbulence set in (Peralta & Melatos 2009; Melatos & Peralta 2010). …”
mentioning
confidence: 99%